Violation of The Universal Declaration of Human Rights 1948 for Crimes Against Humanity in Myanmar and China - Fithriatus Shalihah; Muhammad Raka Fiqri; Mohd. Arief (Program Studi Ilmu Hukum Universitas Maritim Raja Ali Haji, 2021)
Since the birth of the Universal Declaration of Human Rights in 1948, it has been a marker and guide in which it is hoped that in the future, there will be no more violations of human rights around the world, every human being has the right to a decent life and a peaceful life, free to embrace religion and life without discrimination, But this is not the case in Myanmar and China. So far, various facts have shown human rights violations committed by the Government of Myanmar and China, acts of discrimination, restrictions on freedom of religious rituals, and acts of severe crimes against humanity such as Genocide. Countries that should be the subject of international law that protects the human rights of their citizens are perpetrators of human rights crimes against them, international organizations such as the United Nations cannot do much in dealing with human rights violations and crimes against humanity that occur, this paper will discuss how the judicial review of UDHR violations against crimes against humanity that occurred in Myanmar and China and how the United Nations should play a role. The research method used is normative legal research using secondary data, primary legal materials, namely the 1948 UDHR and international legal instruments, and secondary legal materials of a literary nature such as books, journals, articles, and newspapers from internet sites that the author considers relevant related to the object written discussion.